Significant Dark Current Suppression in Organic Photodetectors Using Side Chain Fluorination of Conjugated Polymer. (13th October 2021) - Park, Byoungwook; Jung, Juhyoung; Lim, Dae‐Hee; Lee, Hanbee; Park, Sungjun; Kyeong, Minju; Ko, Seo‐Jin; Eom, Seung Hun; Lee, Seung‐Hoon; Lee, Changjin; Yoon, Sung Cheol
Abstract: Dark current density ( J dark ) is the most important factors determining signal‐to‐noise ratio, linear dynamic range and detectivity ( D * ) of organic photodetectors (OPDs). However, the solution‐processed OPDs generally suffer from high J dark under bias because the origin of J dark still remains unclear and related to complicate factors. In this work, the effect of fluorinated alkyl side chain (FAC) of conjugated polymers (CPs) on the OPD performance is systematically investigated according to the number of fluorine atom. The OPDs, comprising the CPs with a FAC (CP‐FAC), exhibit at least two orders lower J dark (≈3.73 × 10 ‐10 A cm ‐2 at ‐2 V) compared to that without FAC while significantly maintaining high external quantum efficiency (≈78%). This is because the side chain fluorination leads to the formation of a more ordered molecular structure of the CPs, which reduces the trap density and energetic disorder, thus resulting in the effective suppression of J dark and in the enhancement of charge carrier mobility. The CP‐FAC based OPD exhibits an exceptionally high D * (≈3.39 × 10 13 cm Hz 1/2 W ‐1 at ‐2 V) and a reasonable response speed (f‐3db = ≈56.31 kHz). Furthermore, a photoplethysmography sensor comprising the CP‐FAC based OPD in a transmission mode is demonstrated. Abstract : The suppression of dark current density directly affects the detectivity of organic photodetectors. This study demonstrates that the fluorination of the alkyl side chains of conjugated polymers can lead to the formation of closely and evenly stacked molecular structures that decreases the number of trap states and degree of energetic disorder, thereby effectively suppressing the dark current density.